2018
DOI: 10.1186/s12920-018-0335-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome analysis reveals differential gene expression profile reflecting macrophage polarization in response to influenza A H5N1 virus infection

Abstract: Our study provides important mechanistic insights into the understanding of H5N1 viral pathogenesis and the multi-faceted host immune responses. The dysregulated genes could be potential candidates as therapeutic targets for treating H5N1 disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…RNA viruses, like influenza virus, can induce potent IFN antiviral responses which are strain and host cell specific(58). A highly relevant transcriptomic profiling of influenza infection in PBMC macrophages correlated an acute type I IFN response with an influenza virus strain with higher pathogenicity(59). Recent reports suggest that acute MNV infection is capable of IFN-response evasion(49), and particularly in the persistent murine norovirus strain MNV-S99(60).…”
Section: Discussionmentioning
confidence: 99%
“…RNA viruses, like influenza virus, can induce potent IFN antiviral responses which are strain and host cell specific(58). A highly relevant transcriptomic profiling of influenza infection in PBMC macrophages correlated an acute type I IFN response with an influenza virus strain with higher pathogenicity(59). Recent reports suggest that acute MNV infection is capable of IFN-response evasion(49), and particularly in the persistent murine norovirus strain MNV-S99(60).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, H3N2 influenza virus subtype-infection induces comparable TNF-α, IL-12, IP-10, and IL-6 levels in both M1-like and M2-like monocytes and macrophages, and both macrophage types could be readily infected with this virus; an observation in marked contrast with the clearly distinct cytokine profiles of M1-like and M2-like macrophages exposed to bacterial products [ 63 ]. When analyzing the whole transcriptome of macrophages infected with highly pathogenic H5N1 influenza virus, another study showed that the activation state of the macrophage population is variable across time, suggesting that macrophage subtype switching is a highly plastic process [ 64 ].…”
Section: Swinging Macrophage Polarization During Infectionsmentioning
confidence: 99%
“…The transcriptome can aggregate a standard of analysis for the M2 phenotype characterized mainly by the expression of M130, CD163, CD206, MRC1, CCR7, МСР-3, FceRII, CD23, GPR86, GPR105, TLR-2, P2Y8, P2Y11, P2Y12, dectin-1, DC-SIGN, CD209, DCIR (CLECSF6), CLACSF13, FIZZ1, ST2 (SR-A, М60), CD184, TRAIL, STAT6, IL-27Ra, Chil3, Retnla, Ppar-γ, ARG1, TGF-β, IL-4, IL-5, IL-10, and IL-13 (Table 1). 85,86 It is noteworthy that transcriptome analysis has enabled elucidation of mechanisms underlying the modulation of IL-4 intracellular signaling by the induction of zinc finger TFs, Egr2, and c-Myc expression. As a final outcome, ingenuity pathway analysis shows that expression of these markers is directly involved in cell cycle progression in tumorigenesis.…”
Section: Markers Of M1 M2 and M4 Macrophagesmentioning
confidence: 99%